The Effects of Bariatric Surgery and Gastrectomy on the Absorption of Drugs, Vitamins, and Mineral Elements - Miłosz Miedziaszczyk; Patrycja Ciabach; Edyta Szałek (MDPI AG, 2021)
Bariatric surgery, which is an effective treatment for obesity, and gastrectomy, which is the primary treatment method for gastric cancer, alter the anatomy and physiology of the digestive system. Weight loss and changes in the gastrointestinal tract may affect the pharmacokinetic parameters of oral medications. Both bariatric and cancer patients use drugs chronically or temporarily. It is important to know how surgery affects their pharmacokinetics to ensure an effective and safe therapy. The Cochrane, PubMed, and Scopus databases were searched independently by two authors. The search strategy included controlled vocabulary and keywords. Studies show that bariatric surgery and gastrectomy most often reduce the time to maximum plasma concentration (tmax) and decrease the maximum plasma concentration (Cmax) in comparison with the values of these parameters measured in healthy volunteers. Vitamin and mineral deficiencies are also observed. The effect depends on the type of surgery and the properties of the drug. It is recommended to use the drugs that have been tested on these groups of patients as it is possible to monitor them.